Profile of Secondary Glaucoma at a Tertiary Hospital in East Java - Komaratih, Evelyn; Rindiastuti, Yuyun; Primitasari, Yulia (Folia Medica Indonesiana, 2020)
Glaucoma is the leading cause of irreversible blindness. The aim of this study was to review the profile of secondary glaucoma cases visiting a tertiary hospital in East Java. This is retrospective observational study, completed case records of new patients with secondary glaucoma who presented to glaucoma clinic from January 2014 to April 2016 were included. Out of the 363 case records screened, 66 cases were found to eligible for inclusion. The evaluation included a detailed history and examination performed including vision, anterior segment examination, intraocular pressure (IOP), gonioscopy, and fundus evaluation. Diagnosis of secondary glaucoma was made on the basis of presence of a secondary cause for presence of raised IOP. 66 cases were eligible for inclusion in the study, most of the cases was occurred in the range age 21-50 years. The male female ratio was 1.3:1. Frequent causes of secondary glaucoma were lens factor 30.8%, steroid induced 29.5%, uveitic 20.5%, neovascular15.4%, and surgical complication 3.8%. Most patients with secondary glaucoma have poor vision < 0.1 with high IOP at presentation. Assessment and early detection of underlying cause is the key guide to treatment strategy.